Performance of Rice with Varied Age of Seedlings and Planting Geometry under System of Rice Intensification (SRI) in Farmer’s Field in Western Terai, Nepal - Dahal, Khem R; Khadka, Ram B (Nepal Journal of Science and Technology, 2013)
Numbers of on-farm experiments were conducted to assess the performance of rice ( var. Sabitri) cultivated using System of Rice Intensification (SRI) with varied age of seedlings and planting geometry in four VDCs of Kailali, far western Nepal, under the aegis of Farmers’ Field School (FFS) during the rainy season of 2010. The experiment consisted of the seedlings of four age groups; 8, 15, 22 and 29-days and four planting geometry; 15x15cm2, 20x20cm2, 25x25cm2 and 30x30cm2 planted in four FFSs. Parameters such as number of tillers per hill, effective tillers /m2, 1000 seed weight (TGW) and grain yield were recorded. The results showed that 8-days-old seedlings produced significantly higher number of tillers per hill (40) and effective tiller per m2 (373), higher 1000 seed weight (21.10 g), grain yield (7.8ton/ha), net return (Rs.71900/ha) and B:C ratio (1.594). Similarly, crop planted in the geometry of 25x25 cm2 produced significantly higher number of tillers per hill(36), effective tiller per m2 (328), higher 1000 grain weight (21.50 g), grain yield (8.54mt/ha), net return (Rs.83350/ha) and B:C ratio (1.84). Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 1-6 DOI: http://dx.doi.org/10.3126/njst.v13i2.7706